New nomenclature in Syzygium (Myrtaceae) from Indonesia and its vicinities - Pudji Widodo (Research Center for Biology, 2012)
Current generic concepts in Myrtaceae suggest that nearly all Old World taxa originally described in Eugenia L. and Jambosa Adans. should be accommodated within Syzygium P. Br. ex Gaertn. Six new combinations and a new name in Syzygium are proposed. Complete synonymy and typifications are given.